Poplar MYB117 promotes anthocyanin synthesis and enhances flavonoid B-ring hydroxylation by up-regulating the flavonoid 3′, 5′-hydroxylase gene. (12th March 2021) - Ma, Dawei; Tang, Hao; Reichelt, Michael; Piirtola, Eerik-Mikael; Salminen, Juha-Pekka; Gershenzon, Jonathan; Constabel, C Peter
Abstract : Flavonoid biosynthesis is regulated by MYB transcription factors in plants. Here we characterize a new poplar MYB activator, MYB117, that promotes anthocyanin accumulation and flavonoid B-ring hydroxylation. Abstract: Flavonoids, such as anthocyanins, proanthocyanidins, and flavonols, are widespread plant secondary metabolites and important for plant adaptation to diverse abiotic and biotic stresses. Flavonoids can be variously hydroxylated and decorated; their biological activity is partly dependent on the degree of hydroxylation of the B-ring. Flavonoid biosynthesis is regulated by MYB transcription factors, which have been identified and characterized in a diversity of plants. Here we characterize a new MYB activator, MYB117, in hybrid poplar ( Populus tremula×tremuloides ). When overexpressed in transgenic poplar plants, MYB117 enhanced anthocyanin accumulation in all tissues. Transcriptome analysis of MYB117 -overexpressing poplars confirmed the up-regulation of flavonoid and anthocyanin biosynthesis genes, as well as two flavonoid 3′, 5′-hydroxylase (F3′5′H) genes. We also identified up-regulated cytochrome b 5 genes, required for full activity of F3′5′H . Phytochemical analysis demonstrated a corresponding increase in B-ring hydroxylation of anthocyanins, proanthocyanidins, and flavonols in these transgenics. Similarly, overexpression of F3′5′H1 directly in hybrid poplar also resulted in increased B-ring hydroxylation, but without affecting overall flavonoid content. However, the overexpression of the cytochrome b 5 gene in F3′5′H1 -overexpressing plants did not further increase B-ring hydroxylation. Our data indicate that MYB117 regulates the biosynthesis of anthocyanins in poplar, but also enhances B-ring hydroxylation by up-regulating F3′5′H1 .